Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Carbon and phosphorus regeneration during organic matter decomposition in aquatic ecosystems: characteristics, mechanisms, and environmental effects - Chao Yin; Yan Zeng; Jingan Chen; Peng Liao; Jia Yu; Guangrong Ran; Baohua Xiao; Xudong Guo; Ziyan Zhang; Jingfu Wang; Haiquan Yang; Quan Yuan (Geochimica et Cosmochimica Acta, 2026)

Recent advances in the design mechanisms of mitochondrial fluorescent probes: A review - Fei Peng; Bo Wang; Yunjia Xu; Ran Chai; Aibing Wu; Mingming Xue; Huijuan Tian; Yan Lv; Xiangyu Guo; Bin Hao; Baoxiang Gao (Analytica Chimica Acta, 2026)

Multi-objective optimization of urban residential morphology in cold regions based on energy consumption reduction and solar radiation utilization potential enhancement - Peng Cui; Zixin Guo; Yang Song; Yewei Zheng; Ran Ji; Jiaqi Lu (Sustainable Cities and Society, 2026)

Autophagy is more vital in tomato and citrus than in arabidopsis - Guowang Liao; Haoyang Hu; Peng Zhang; Ran Hu; Saiyu Cao; Ye Guo; Pengwei Wang (Protoplasma, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Distinct profiles and elevated exposure to liquid crystal monomers in urban areas: Insights from indoor dust across China - Ye-Yang Hou; Da-Jian Li; Shi-Yang Liu; Peng-Ran Guo; Liang-Ying Liu (Environmental Research, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Research on the influencing factors and prediction model of carbon storage of urban forest in Harbin, China - Peng Cui; Yewei Zheng; Lei Wang; Jiajie Tian; Ran Ji; Zixin Guo (Urban Forestry & Urban Greening, 2026)

A metabolomics study unravels the hepatotoxic mechanism of diuron in zebrafish: Disruption of glutathione synthesis and mitochondrial energy metabolism - Jingjing Shi; Tianlie Luo; Zhuang Wang; Xi Ren; Yueyu Ran; Yuehan Peng; Guo Liu; Willie Peijnenburg (Aquatic Toxicology, 2026)

Preliminary design and analysis of a radar system model based-on a phased-array RF astro-receiver for space debris detection and tracking - Lalida Tantiparimongkol; Ming Shen; Peng-qi Gao; Xiao-zhong Guo; Huan-huan Yu; Jia-wei Li; Jia-lang Ding; Yu-ting Chu; Ran Duan; You Zhao (Advances in Space Research, 2026)

Resistance mechanisms and fitness outcomes of tetraniliprole, one novel diamide insecticide, in a near-isogenic strain of Spodoptera litura (Lepidoptera: Noctuidae) - Peng Lu; Ren Li; Xiao Guo; Juan Tang; Yilu Tong; Shengran Zhang; Qi Su; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

Enhanced bacteria-fungi associations and soil microbial network stability underpin ecosystem multifunctionality across a 53-year desert restoration chronosequence - Qingqing Hou; Muhammad Aqeel; Longwei Dong; Jie Peng; Ying Sun; Fan Li; Dong Tang; Bodong Yuan; Xusheng Guo; Jinzhi Ran; Weigang Hu; Xinrong Li; et al. (Journal of Environmental Management, 2026)

Keystone microbes mediate root traits and phosphorus uptake to enhance maize crop productivity in intercropping systems - Yi-Wen Zhao; Ran An; Jiu-Dong Zhang; Rui-Peng Yu; Yi Xing; Xing-Guo Bao; Jing-Jing Peng; Long Li (Plant and Soil, 2026)

Identifying the contribution of urban input to river microplastics: From the upper reach to estuary - Haiyan Ran; Qixin Wu; Meixue Peng; Shilin Gao; Mingzhe Guo; Jie Zeng; Hao Xia (Journal of Hydrology, 2025)

Resveratrol ameliorates Salmonella Typhimurium-induced intestinal inflammation and barrier dysfunction in chickens via COX-2 inhibition - Yaochen Xie; Shenghong Chen; Dingqian Guo; Hui Peng; Xuhua Ran; Xiaobo Wen (Research in Veterinary Science, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Amine-Functionalized SiC nanowires aerogel synchronizes high capacity and ultra-rapid kinetics for CO2 capture - Yanni Ran; Kang Peng; Ziyan Li; Xingwang Guo; Honglin Chen; Shengxuan Cai; Lei Su; Min Niu; De Lu; Hongjie Wang (Chemical Engineering Journal, 2025)

How the dispersion and coalescence behaviors of CO2 bubbles affecting carbonation reaction in bubble column reactor: experimental and numerical simulation study - Lin Chen; Jintao Ma; Cheng Chen; Xin Wang; Yonghong Qin; Enze Li; Yanxia Guo; Ran Peng; Zihe Pan (Chemical Engineering Journal, 2025)

Assessing river-blocking risks of ancient landslide in mountainous regions: insights from a slow-moving, high-position reactivated ancient landslide in the Southeast Tibetan Plateau - Xinfu Xing; Changbao Guo; Tanfang Zhu; Peng Xin; Hao Yuan; Yiqiu Yan; Congyan Ran (Bulletin of Engineering Geology and the Environment, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Highly dispersed WOm enables efficient reductive debenzylation of hexabenzylhexaazaisowurtzitane (HBIW) over bifunctional Pd-WOm/CeO2 - Qing-Shan Niu; Yi-Ran Du; Xin-Peng Guo; Jing-Wen Sun; Si-Ping Pang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

EDDS application destabilizes soil organic matter in phytoremediation: Insights from quantity and molecular composition of dissolved organic matter - Yan-ping Zhao; Peng-ran Guo; Zhi-liang Chen; Jin-li Cui; Jian-xu Wang; Chao Chen; Hang Wei; Cheng Wang (Environmental Research, 2024)

Biogenic silica dynamics in coastal wetland sediments: A key driver of silicon and carbon biogeochemical cycling - Xiangwei Zhao; Zhaoliang Song; Yuntao Wu; Lukas Van Zwieten; Laodong Guo; Changxun Yu; Zimin Li; Lele Wu; Xiaomin Yang; Xiangbin Ran; Jun Sun; Yuqiu Wei; et al. (Limnology and Oceanography, 2024)
Biogenic silica (biogenic Si) is a bioactive component crucial for the biogeochemical cycling of Si in terrestrial and aquatic ecosystems. Its formation and dissolution dynamics are intricately linked to carbon (C) cycling. However, knowledge about the source, composition, and factors controlling the distribution of biogenic Si in coastal wetland sedimentary environments is still limited. To address this lack of knowledge, we introduced a suite of geometric models for biogenic Si biovolume calculation and investigated biogenic Si assemblages, along with biogenic Si and biogenic Si‐occluded C contents, in sediments from representative coastal wetlands along the west coast of Bohai Bay. Our analysis showed that sedimentary biogenic Si predominantly derived from phytoliths (78.1% ± 5.8%), diatoms (18.2% ± 4.8%), and sponge spicules (3.7% ± 2.9%). Notably, phytolith assemblages were primarily composed of forms derived from the Poaceae family. The biogenic Si‐occluded C content (0.035–1.870 g kg −1 ) within these wetland sediments was consistent across both sites, accounting for 0.97–5.71% of the total organic C pool. Structural equation modeling indicated that total organic C, pH, and amorphous aluminum oxides either directly or indirectly influenced the biogenic Si content in coastal wetlands sediments. These results demonstrate the critical role that biogenic Si plays in the Si biogeochemical cycle and provide valuable information that advances our understanding of the biogeochemical interactions between Si and C in coastal wetland ecosystems.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Effects of Aeromonas infection on the immune system, physical barriers and microflora structure in the intestine of juvenile grass carp (Ctenopharyngodon idella) - Meixing Guo; Ran Peng; Kelan Jin; Xia Zhang; Huilan Mo; Xiang Li; Fufa Qu; Jianzhou Tang; Shenping Cao; Yonghua Zhou; Zhimin He; Zhuangwen Mao; et al. (Fish & Shellfish Immunology, 2024)

Efficient and low-energy degradation of chlorobenzene via catA-mediated cleavage and bedC1 docking in a novel Burkholderia stabilis TF-2 - Zhilin Xing; Fang Gou; Xiaoping Zhang; Yanhui Gao; Xihong Ke; Dongni Ran; Peng Wang; Jiangfeng Guo; Heng Wu; Chao Peng; Tiantao Zhao (Chemosphere, 2024)

GEO satellite on-orbit refueling and debris removal hybrid mission planning under uncertainty - Weikui Liang; Hui Zhi; Peng Han; Guangtao Ran; Guangfu Ma; Yanning Guo (Advances in Space Research, 2024)

Porous carbon prepared by thermal dissolution of coal and biomass for high-performance supercapacitors - Yi Liu; Wei-Dong Cao; Xing Fan; Ran-Ran Hou; Xiang Bai; Xiao-Yun Zhang; Yan Li; Guo-Ming Zhao; Peng Liang (Fuel, 2024)

Uptake, subcellular distribution, and fate of tetracycline in two wetland plants supplemented with microbial agents: Effect and mechanism - Jie Zhong; Hang Wei; Jian-Xiong Xie; Yu-Hui Wu; Bing Tang; Qi Zou; Peng-Ran Guo; Zhi-Liang Chen (Journal of Environmental Management, 2024)

Novel insights into the protective effects of leonurine against acute kidney injury: Inhibition of ER stress-associated ferroptosis via regulating ATF4/CHOP/ACSL4 pathway - Ran Cheng; Xiaowan Wang; Lihua Huang; Zhisheng Lu; Aijun Wu; Shan Guo; Chuang Li; Wei Mao; Ying Xie; Peng Xu; Ruimin Tian (Chemico-Biological Interactions, 2024)

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

Electrocatalytic degradation of Favipiravir by heteroatom (P and S) doped biomass-derived carbon with high oxygen reduction reaction activity - Shi-Ting Huang; Yong-Qian Lei; Peng-Ran Guo; Hong-Xin Chen; Shu-Chai Gan; Zeng-Hui Diao (Chemical Engineering Journal, 2024)

Effects of nitrogen application on physicochemical properties of rice starch under elevated temperature - Wenzhe Liu; Kailu Wang; Yufei Zhao; Yingying Shen; Chen Zhang; Yuxuan Peng; Xuan Ran; Hao Guo; Yanfeng Ding; She Tang (Food Chemistry, 2024)

Seismic performance of special-shaped hexagonal concrete filled steel tubes with inner diaphragm plates and shear studs - Bai-Xiang Wang; Ran Ding; Jian-Guo Nie; Cui-Kun Wang; Peng Liu; Cheng-Hua Wang (Engineering Structures, 2024)

Mitigating the adverse effect of warming on rice canopy and rhizosphere microbial community by nitrogen application: An approach to counteract future climate change for rice - Yingying Shen; Lei Xu; Hao Guo; Hashmi Ismail; Xuan Ran; Chen Zhang; Yuxuan Peng; Yufei Zhao; Wenzhe Liu; Yanfeng Ding; She Tang (Science of The Total Environment, 2023)

Monocarboxylate transporter blockage-enabled lactate redistribution reshapes immunosuppressive tumor microenvironment and enhances chemodynamic immunotherapy - Jingxue Wang; Weixi Jiang; Mingxiao Fang; Chier Du; Xun Guo; Xiaoling Qiu; Xiaoting Wang; Yuanli Luo; Peng Tu; Chen Cheng; Pan Li; Haitao Ran; et al. (Chemical Engineering Journal, 2023)

Degradation of Levofloxacin by a green zero-valent iron-loaded carbon composite activating peroxydisulfate system: Reactivity, products and mechanism - Shi-Ting Huang; Yong-Qian Lei; Peng-Ran Guo; Wen-Xuan Zhang; Jing-Yi Liang; Xie Chen; Jing-Wei Xu; Zeng-Hui Diao (Chemosphere, 2023)

A numerical study on desalination performance enhancement by bipolar ionic diode nanochannels - Tong Li; Ran Peng; Tingting Zhang; Chenjie Wang; Linan Guo; Yongxin Song; Junsheng Wang; Minyi Xu (Desalination, 2023)

Medium-chain triglyceride-stabilized docetaxel-loaded HSA nanoparticles effectively inhibited metastatic non-small cell lung cancer - Yunlong Cheng; Xiaoying Pang; Jing Wu; Lingling Zhou; Jinxu Cao; Liuchang Wang; Kang Qian; Peng Yang; Minjun Xu; Dongyu Sheng; Ran Meng; Pengzhen Wang; et al. (Drug Delivery and Translational Research, 2023)

Simultaneous determination of twelve natural estrogens in dairy milk using liquid–liquid extraction and solid-phase extraction coupled with gas chromatography-mass spectrometry - De-ming Kong; Zhao Tang; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Yu Liu (Environmental Science and Pollution Research, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

High-pressure synthesis of fully sp2-hybridized polymeric nitrogen layer in potassium supernitride - Minghong Sui; Shuang Liu; Peng Wang; Nianlong Zou; Qing Dong; Miao Zhou; Shifeng Niu; Lei Yue; Zitong Zhao; Linlin Guo; Bo Liu; Ran Liu; et al. (Science Bulletin, 2023)

Alpha-ketoglutarate alleviates cadmium-induced inflammation by inhibiting the HIF1A-TNFAIP3 pathway in hepatocytes - Yinzhao Jia; Chuanzheng Yin; Wenbo Ke; Jing Liu; Bing Guo; Xiaofei Wang; Peng Zhao; Shaobo Hu; Chen Zhang; Xuan Li; Ran Liu; Xichuan Zheng; et al. (Science of The Total Environment, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Molecular mechanisms of adaptive evolution in wild animals and plants - Yibo Hu; Xiaoping Wang; Yongchao Xu; Hui Yang; Zeyu Tong; Ran Tian; Shaohua Xu; Li Yu; Yalong Guo; Peng Shi; Shuangquan Huang; Guang Yang; et al. (Science China Life Sciences, 2023)

Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency - Peiyan Yang; Peng Zhang; Yali Deng; Yinghao Liao; Xinxin Guo; Mingjun Sun; Lihong Yin; Ran Liu (Environmental Pollution, 2023)

Adsorption of Cd on Soils with Various Particle Sizes from an Abandoned Non-ferrous Smelting Site: Characteristics and Mechanism - Zhichao Jiang; Zhaohui Guo; Chi Peng; Richmond Anaman; Hongzhen Ran; Xiyuan Xiao (Bulletin of Environmental Contamination and Toxicology, 2022)

Effects of combined soil amendments on Cd accumulation, translocation and food safety in rice: a field study in southern China - Lei Shi; Zhaohui Guo; Shuaixia Liu; Xiyuan Xiao; Chi Peng; Wenli Feng; Hongzhen Ran; Peng Zeng (Environmental Geochemistry and Health, 2022)

Dynamic monitoring of surface water in the Tibetan Plateau from 1980s to 2019 based on satellite remote sensing images - Hui-chan Liu; Guo-jin He; Yan Peng; Gui-zhou Wang; Ran-yu Yin (Journal of Mountain Science, 2021)

Screening maize (Zea mays L.) varieties with low accumulation of cadmium, arsenic, and lead in edible parts but high accumulation in other parts: a field plot experiment - Ningke Yang; Hongbin Wang; Haijuan Wang; Zhongzhen Wang; Jiakang Ran; Siyu Guo; Yu Peng (Environmental Science and Pollution Research, 2021)

The effect of consecutive ambient air pollution on the hospital admission from chronic obstructive pulmonary disease in the Chengdu region, China - Yi Zhang; Ziyue Wang; Yu Cao; Lifu Zhang; Guan Wang; Fangjie Dong; Ren Deng; Baogen Guo; Li Zeng; Peng Wang; Ruimei Dai; Yu Ran; et al. (Air Quality, Atmosphere & Health, 2021)

Comprehensive Marine Observing Experiment Based on High-Altitude Large Unmanned Aerial Vehicle (South China Sea Experiment 2020 of the “Petrel Project”) - Xuefen Zhang; Liangxu Li; Rongkang Yang; Ran Guo; Xia Sun; Jianping Luo; Hongbin Chen; Daxin Liu; Kebing Tang; Wenwu Peng; Xiaodong Han; Qiyun Guo; et al. (Advances in Atmospheric Sciences, 2021)

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Hemicellulose modification promotes cadmium hyperaccumulation by decreasing its retention on roots in Sedum alfredii - Xinyu Guo; Yuankun Liu; Ran Zhang; Jipeng Luo; Yuchao Song; Jinxing Li; Keren Wu; Liangcai Peng; Yuying Liu; Yilin Du; Yongchao Liang; Tingqiang Li (Plant and Soil, 2020)

Correction to: Urinary metabolites of polycyclic aromatic hydrocarbons in pregnant women and their association with a biomarker of oxidative stress - Xiang-Ying Lou; Peng-Ran Wu; Ying Guo (Environmental Science and Pollution Research, 2020)

Urinary metabolites of polycyclic aromatic hydrocarbons in pregnant women and their association with a biomarker of oxidative stress - Xiang-Yin Lou; Peng-Ran Wu; Ying Guo (Environmental Science and Pollution Research, 2019)

Co-seismic surface rupture of Papatea fault and reactivation mechanism of the Clarence landslide during the 2016 Mw7.8 Kaikoura earthquake, New Zealand - Peng Guo; Zhu-jun Han; Hong-liu Ran; Jia-hong Luo; Guo Wu; Ren-mao Yuan (Bulletin of Engineering Geology and the Environment, 2019)

Effects of mixed amendments on the phytoavailability of Cd in contaminated paddy soil under a rice-rape rotation system - Hongzhen Ran; Zhaohui Guo; Lei Shi; Wenli Feng; Xiyuan Xiao; Chi Peng; Qinghua Xue (Environmental Science and Pollution Research, 2019)

Perfluoroalkyl Substances in Water from the Yangtze River and Its Tributaries at the Dividing Point Between the Middle and Lower Reaches - Ke-Yan Tan; Guo-Hui Lu; Xin Yuan; Yu Zheng; Peng-Wei Shao; Jing-Yi Cai; Yi-Ran Zhao; Xiao-Hua Zhu; Yong-Liang Yang (Bulletin of Environmental Contamination and Toxicology, 2018)

Amyloid β-Derived Diffusible Ligands (ADDLs) Induce Abnormal Autophagy Associated with Aβ Aggregation Degree - Jie Wen; Fang Fang; Shu-Han Guo; Ying Zhang; Xiang-Lei Peng; Wei-Min Sun; Xiao-Ran Wei; Jin-Sheng He; Tao Hung (Journal of Molecular Neuroscience, 2018)

A Randomized Study to Compare the Analgesic Efficacy of Ultrasound-Guided Block of Fascia Iliaca Compartment or Femoral Nerve After Patella Fracture Surgery - Mingjian Kong; Ran Guo; Jianqing Chen; Peng Li; Zhen Wu (Cell Biochemistry and Biophysics, 2015)

Response of the bacterial diversity and soil enzyme activity in particle-size fractions of Mollisol after different fertilization in a long-term experiment - Ning Ling; Yuming Sun; Jinghua Ma; Junjie Guo; Ping Zhu; Chang Peng; Guanghui Yu; Wei Ran; Shiwei Guo; Qirong Shen (Biology and Fertility of Soils, 2014)